Steady State Economy at Optimal Population Size - Theodore Lianos (The White Horse Press, 2018)
This paper reviews briefly the idea of a steady state economy from the ancient times to the present. It discusses some of the suggestions made by H. Daly in his model of a steady state economy and particularly the idea of a stable population. It suggests that population must be stable at a level that is compatible with ecological equilibrium. That level is about three billion people and therefore the world population must be reduced drastically. This can be achieved if each family is allowed to have less than two children. To achieve this reduction of population this paper proposes the creation of an international market for human reproduction rights.